Static VAr compensator based reactive power management for SOFC power plants - Uzunoglu, M.; Onar, O. C. (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper reports the dynamic behavior of a solid-oxide fuel cell (SOFC) power plant including a battery bank and a static Volt-Ampere-reactive power compensator system (static VAr compensator or SVC) for active and reactive power flow controllers. First, the necessities of the reactive power management as well as the load following capability of distributed generation (DG) systems are emphasized. Then, a decoupled active and reactive power management control strategies are described. in the proposed system, while the active power management is achieved using the SOFC power plant with the aid of the battery; the reactive power management is achieved using an SVC system which totally prevents the reactive loading interactions with the dc bus. The simulation results of the integrated overall system indicate the viability of the proposed management strategies.(c) 2008 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: battery systems; dynamic modeling; reactive power management; solid oxide fuel cell; static VAr compensator; PEM FUEL-CELL; DYNAMIC-BEHAVIOR; SYSTEM; MODEL; SIMULATION; Chemistry; Electrochemistry; Energy & Fuels